1999
DOI: 10.1096/fasebj.13.6.707
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of hemopoietic cell cycling in mice suggests its involvement in organismal life span

Abstract: Normal somatic cells undergo replicative senescence in vitro but the significance of this process in organismic aging remains controversial. We have shown previously that hemopoietic stem cells of common inbred strains of mice vary widely in cycling activity and that this parameter is inversely correlated with strain‐dependent mean life span. To assess whether cell cycling and life span are causally related, we searched for quantitative trait loci (QTLs) that contributed to variation of these traits in BXH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 47 publications
4
56
0
1
Order By: Relevance
“…There are other loci reaching a genome-wide suggestive linkage level including D2Rik63 (Chr 2, 69.0 cm, LOD 3.7, P 3.9 Â 10 25 ), Ms6hm (Chr 4, 40.3 cm, LOD 2.2, P 1.5 Â 10 23 ), D7Ncvs. (Chr 7, 6.0 cm, LOD 3.4, P 6.5 Â 10 25 ), and D11Rik100 (Chr 11, q 2001 Blackwell Science Ltd, Scandinavian Journal of Immunology, 54, 10±20 31.0 cm, LOD 2.1, P 1.8 Â 10 23 ) and others [17]. Table 1 shows the results of independent linkage analyses of four phenotypes: three traits in the haematopoietic system, and the mean lifespan of BXD mice.…”
Section: Quantitative Trait Loci (Qtls) Affecting the Haematopoietic mentioning
confidence: 99%
See 1 more Smart Citation
“…There are other loci reaching a genome-wide suggestive linkage level including D2Rik63 (Chr 2, 69.0 cm, LOD 3.7, P 3.9 Â 10 25 ), Ms6hm (Chr 4, 40.3 cm, LOD 2.2, P 1.5 Â 10 23 ), D7Ncvs. (Chr 7, 6.0 cm, LOD 3.4, P 6.5 Â 10 25 ), and D11Rik100 (Chr 11, q 2001 Blackwell Science Ltd, Scandinavian Journal of Immunology, 54, 10±20 31.0 cm, LOD 2.1, P 1.8 Â 10 23 ) and others [17]. Table 1 shows the results of independent linkage analyses of four phenotypes: three traits in the haematopoietic system, and the mean lifespan of BXD mice.…”
Section: Quantitative Trait Loci (Qtls) Affecting the Haematopoietic mentioning
confidence: 99%
“…Two QTLs, on Chr. 7 and 11, are important in regulating the rate of proliferation of haematopoietic progenitor cells [17]. Two loci on Chr.…”
Section: Quantitative Trait Loci (Qtls) Affecting the Haematopoietic mentioning
confidence: 99%
“…Very elegant studies by several investigators have shown that, even within the same species, not all HSCs are created equal and that the HSCs of these two strains of mice have different genetically encoded proliferation and self-renewal potential, with C57BL/6J HSCs undergoing about 30 replications before senescence whereas the DBA2 stem cells are shorter-lived and undergo only about 20 replications before senescence or terminal differentiation. These studies were based on the generation of chimeric mice by combining C57BL/6J and DBA2 embryos [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple adult stem cell types in normal mice have shown age-related reductions in functional capacity (Bergman et al, 1996;de Haan and Van Zant, 1999a,b;Chen et al, 2000;Schlessinger and Van Zant, 2001), but presumably at a slower rate than in p53þ/m mice. In fact, Van Zant and colleagues have shown that depletion of hematopoietic stem cell (HSC) function with aging varies according to strain (de Haan and Van Zant, 1999b;Geiger et al, 2001;Schlessinger and Van Zant, 2001). Interestingly, they have correlated an early reduction in HSC function with short lived strains and prolonged HSC function with long lived strains.…”
Section: P53 Stem Cells and Organismal Aging: A Modelmentioning
confidence: 99%